Glaucoma Research: A Scientometric Study of Indian Publications Output, 2002-11 - Gupta, Ritu; Gupta, B.M.; Kshitij, Avinash; Bala, Adarsh (DESIDOC Journal of Library & Information Technology, 2014)
The study analyses the Indian publications output in glaucoma research during 2002-11 on different parameters including contribution & citation impact of top most productive countries, India’s overall contribution, its growth pattern and citation impact, the share of international collaboration in India’s overall research output, contribution of leading countries and identification of leading foreign collaborating partners, Indian contribution & impact of different types of glaucoma, glaucoma research by sub-fields and glaucoma research output by different population age groups, productivity and impact of leading Indian institutions and authors and pattern of communication of Indian output in most productive journals. The Scopus citation database has been used to retrieve the data for 10 years (2002-11) by searching the keywords ‘glaucoma or intraocular pressure’ in combined Title, Abstract and Keywords field. The Indian publications output in glaucoma research (1078 papers) during 2002-11 increased from 61 papers in 2002 to 207 papers in 2011, witnessing an annual average growth rate of 18.29 %. The average citation impact per paper registered by Indian publications in glaucoma research was 3.03 during 2002-11, which decreased from 3.87 during 2002-06 to 2.49 during 2007-11. The international collaborative share of India in overall glaucoma research was 21.06 % during 2002-11, which increased from 17.92 % during 2002-06 to 23.09 % during 2007-11. The glaucoma’s irreversibility, lacking of glaucoma specialists and patients unawareness demand for an economic and effective glaucoma diagnosis system for screening. Disease control and elimination require an adequately trained functional workforce with an enabling infrastructure and technology. The authors suggest that research efforts needs to be strengthened quiet substantially by way of investment in R&D. Both research output and quality of research should be increased and strengthened and international collaborative research may further be widened to learn from the experiences of other countries. DESIDOC Journal of Library & Information Technology, 2014, 34(1), pp. 35-45. http://dx.doi.org/10.14429/djlit.34.5944